Economic Cooperation of ASEM Countries and the Trade in Textiles between the European Union and Asian Countries - Drzymała, Agnieszka (Comparative Economic Research. Central and Eastern Europe, 2019)
The paper covers the issues of dialogue and cooperation between ASEM countries in the conditions of growing mutual international interdependencies and changing conditions of cooperation at the global level. It presents the ASEM countries which are taking steps aimed at deepening mutual relations. The paper shows one of the many aspects of mutual cooperation. The total trade between the parties is discussed, with a particular focus on the trade in textiles under ASEM. The time range includes the latest available statistics for the period 2013–2016. The data analysis provides the basis for verifying the thesis that the European Union countries import more textiles and clothing than they export to Asian ASEM countries.